The Effectiveness of Using Digital Technology (QRIS) in the Payment System for the Development of MSMEs of Metro City - Lestari, Enny Puji; Alimuddin, Agus; Syahpira, Jeni; Wati, Rubianti Novita Irma (Fakultas Studi Islam Universitas Islam Kalimantan Muhammad Arsyad Al Banjary, 2024)
Micro, Small and Medium Enterprises (MSMEs) are productive activities carried out by individuals, or groups that meet the micro-enterprise criteria. This sector acts as a community's economic driver. This study aims to analyze the effectiveness of the use of QRIS digital technology (Quick Response Code Indonesia Standard) on the payment system for the development of MSMEs in Metro City. The research method used quantitatively with a sample of 100 MSME owners in the city of Metro. Data is collected through surveys and analysis of the test of validity, reliability, linear regression Erganda, T test, F test and coefficient of determination. The results showed the qris effectiveness and the use of QRIS digital technology had a positive and significant effect on the development of the MSMEs of Metro City. The T test shows the value of the effectiveness (2,697), and digital qris technology (7,610) greater than t table (1,984) with significance <0.05. F Test Reats F count (623.453)> F table (,09) with a significance of 0.000. CoefficitationPinasi (R2) The amount of 0.928 shows that 92.8% of the development of MSME development can be explained by the effectiveness and use of QRIS digital technology. This study concluded that the use of QRIS was effective in supporting MSME driving in Metro City, Dengfan indicators of timing and operational efficiency.